Mastering Django core : the complete guide to Django 1.8 LTS : delivers absolutely everything you will ever need to know to become a master Django programmer /: the complete guide to Django 1.8 LTS : delivers absolutely everything you will ever need to know to become a master Django programmer. (2016) - George, Nigel
No abstract available